(untitled) - Hamad Atiah J Alsulami, Zafir Khan Mohamed Makhbul (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Surprisingly, taxonomies of Precarious Employment in all facets remain a debatable and unresolved issue in the literature, and this will always matter. The present paper explains the core aspects and boundaries of Precarious Employment in terms of definition, dimensions, influencing factors and the consequences of this phenomenon. Several scholarly scientific databases were searched with certain keywords for scholarly peer-reviewed articles reporting results about employment precariousness, conducted between Jan 2019 and Jan 2020. Following the Snowballing Guidelines for systematic literature studies, further qualitative analysis was used to develop the taxonomies of employment precariousness. The paper found no universal definition or boundaries of precarious employment, yet, with some intersections toward the standard and nonstandard employments; the precariousness phenomenon is reported by hundreds of studies and can be identified in terms of certain dimensions. The paper also found that precariousness in employment can be influenced by many factors including, but not limited to, globalization and global unevenness, markets and work reforms, financial crisis, and economic recession, neoliberalism and liberalization, technological evolution, the role of unions and market deregulation, as well as, organizational restructuring, downsizing, and outsourcing. The paper then identified several consequences of this phenomenon with positive and/or negative impact on flexibility, employability, social aspects, economic inequalities, as well as, the attitudes wellbeing and performance of employees. The application of the taxonomic scheme in this paper provides a systematic organization of employment precariousness and contributes to the classification of knowledge in the area of interest. Therefore, this paper attempted to deepen and bring further insights into the boundaries of precariousness in employment, yet, recommends that our understanding in this area must be widened.